ACHIEVING NEW DIRECTIONS IN SECOND LANGUAGE CLASSROOM THROUGH MULTIPLE INTELLIGENCES APPROACH - Nanquil, Luisito Manalansan (LLT Journal: A Journal on Language and Language Teaching, 2020)
Several classroom cases showed failure or frustration in achieving learning outcomes even if the language teachers have done their best to facilitate and evaluate learning experiences of students. It is the intention of the reviewer/researcher to analyze the book of Armstrong and assess possible insights and practices beneficial to language teachers and other educators in their quest for quality instruction. This paper reflects a lot of classroom realities, challenges, and transitions in relation to how MI approach and instructional strategies should be implemented in the language settings. Other specialties in the classroom may attempt to blend MI approach with other perspectives and practices which could enhance teaching-learning aspects or domains. If all educational centers and institutions will adopt multiple intelligences theory, learners could get the chance to explore their potentials and develop their work skills.